2013
DOI: 10.1167/13.5.16
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between luminance and color signals: Effects on shape

Abstract: Although luminance and color are thought to be processed independently at early stages of visual processing, there is evidence that they interact at later stages. For example, chromatic information has been shown to enhance or suppress depth from luminance depending on whether chromatic edges are aligned or orthogonal with luminance edges. Here we explored more generally how chromatic information interacts with luminance information that specifies shape from shading. Using a depth-matching task, we measured pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 74 publications
(120 reference statements)
1
13
0
Order By: Relevance
“…Given the variability in previous investigations examining the relationship between the perception of spatial, chromatic and achromatic information (e.g. Clery et al, ; Miquilini et al, ; Shapley & Hawken, ; Shevell & Kingdom, ), we recommend such combined thresholds be confirmed using contextualized behavioural experiments. For more information on the mechanism of the RNL clustering as well as the combination and weighting of chromatic and achromatic thresholds see the Supplemental Material.…”
Section: Methodsmentioning
confidence: 97%
“…Given the variability in previous investigations examining the relationship between the perception of spatial, chromatic and achromatic information (e.g. Clery et al, ; Miquilini et al, ; Shapley & Hawken, ; Shevell & Kingdom, ), we recommend such combined thresholds be confirmed using contextualized behavioural experiments. For more information on the mechanism of the RNL clustering as well as the combination and weighting of chromatic and achromatic thresholds see the Supplemental Material.…”
Section: Methodsmentioning
confidence: 97%
“…2,8,9,[44][45][46][47][48] In addition, it has been reported that higher luminance contrast generally induces larger perceived depth. 45,[50][51][52][53][54][55][56][57][58] Thus, the improvement by the luminance gradient might have resulted from visual interpretation of the luminance gradient as shading along with the higher luminance contrast.…”
Section: Effects Of the Spbr-inherent Luminance Gradientmentioning
confidence: 99%
“…As mentioned above, higher luminance contrast generally produces larger perceived depth. 45,[50][51][52][53][54][55][56][57][58] This lower luminance contrast within the isosurface with the SPBR-inherent luminance gradient was caused by introducing the bright luminance gradient on the dark hillside with the large slant (Fig. 3).…”
Section: Effects Of the Spbr-inherent Luminance Gradientmentioning
confidence: 99%
“…Brightness is a key component of primate colour vision; our brain binds together both chromatic and achromatic (brightness) information when interpreting colourful images (Burns and Shepp 1988;Croner and Albright 1999;Clery et al 2013). Brightness is defined as the attribute of a visual sensation where a stimulus is perceived to be more or less intense, based on the achromatic modulation of photoreceptors by the stimulus (Wyszecki and Stiles 1982).…”
Section: Introductionmentioning
confidence: 99%